Four new Teagueia (Orchidaceae: Pleurothallidinae) from the upper Río Pastaza watershed of east-central Ecuador - Jost, Lou; Shepard, Anderson (Lankesteriana: International Journal on Orchidology, 2017)
The genus Teagueia, once considered a minor genus with few species, has undergone a surprisingly diverse local evolutionary radiation in the upper Río Pastaza watershed of the eastern Andes of Ecuador. All species forming this local radiation are long-repent, in contrast to the rest of the species in the genus. Six species from this local radiation have been described previously, and four additional species are described here. The four new species are each distinguished by their particular lip shapes, differences in flower sizes, and differences in leaf textures. The new species, like the others in this radiation, all have extremely narrow distributions.